2009
DOI: 10.1002/14651858.cd002120.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pill for primary dysmenorrhoea

Abstract: Kremser 1971 {published data only} Kremser E, Mitchell GM. Treatment of primary dysmenorrhoea with a combined type oral contraceptive-a double blind study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 29 publications
0
80
0
16
Order By: Relevance
“…Primer dismenorede sıklıkla kullanılan NSAİİ'lerin önerilen dozları Tablo 1' de özetlenmiştir (13,21). (22,23).…”
Section: A-medi̇kal Tedavi̇unclassified
See 1 more Smart Citation
“…Primer dismenorede sıklıkla kullanılan NSAİİ'lerin önerilen dozları Tablo 1' de özetlenmiştir (13,21). (22,23).…”
Section: A-medi̇kal Tedavi̇unclassified
“…Östrojene bağlı bulantı, baş ağrısı, memelerde şiş-kinlik; progesterona bağlı akne, kilo artışı, depresyon görülebilir. Bununla birlikte plasebo kontrollü çift kör çalışmalarda bu yan etkilerin çoğunun benzer olduğu gösterilmiştir (23). Venöz tromboemboli gibi daha ciddi yan etkiler ise çok daha az görülmektedir.…”
Section: öStrojen-progestin İçeren Hormonalunclassified
“…В двух Кокрановских обзорах проанализированы исследования с участием женщин с тяжелой формой ПМС [21], где показано, что уже после трех месяцев примене-ния 20 ЭЭ/ДРСП было существенное снижение частоты и тяжести симптомов (-7,92; 95% ДИ: -11,16 --4,67) у жен-щин, принимавших препарат, и снижение выраженности дисменореи (ОР = 2,01; 95% ДИ: 1,32-3,08) [22]. Современные исследования уделяют внимание и такой стороне КЖ женщины, как ее удовлетворенность сексуаль-ной функцией.…”
Section: обсуждение результатовunclassified
“…12 Effective management of dysmenorrhoea is beneficial for both the afflicted individual and society. Systematic reviews and randomised controlled trials have shown that non steroidal antiinflammatory drugs [13][14][15][16][17] and hormonal regulation through oral contraception 18 are significantly more effective for pain relief than placebo and are often used for symptom control. 19,20 However, some women may not always find them effective or acceptable.…”
Section: Introductionmentioning
confidence: 99%